An approach of developing a system of solid waste treatment - Журавель, Надія Миколаївна; Гужва, Віктор Олексійович (Technology audit and production reserves, 2014)
Nowadays, in Kharkov region, there are problems in the system of treating solid municipal waste. In the paper, it is suggested following the example of foreign countries and implementing a two-stage waste disposal from residential areas by situating a waste transfer station. In this regard, there is a necessity of solving several problems: the problem of locating a station using a graph theory (finding internal or external median); searching an optimal route of waste disposal in a given area (searching Euler’s or Hamiltonian cycle in the graph); selecting the most suitable mark of a waste collection truck out of the available fleet of interchangeable vehicles. Solving these problems would allow reducing fuel consumption, using large-tonnage transport, facilitating a daily work of housing and utilities infrastructure or companies, disposing solid municipal wastes. Furthermore, solving these problems can be united into one software product, which would automate and make calculations for a graph with a large number of state points.